Prevention of contrast-induced acute kidney injury in patients undergoing cardiovascular procedures-a systematic review and network meta-analysis. - Eliano P Navarese; Paul A Gurbel; Felicita Andreotti; Michalina Marta Kołodziejczak; Suetonia C Palmer; Sofia Dias; Antonino Buffon; Jacek Kubica; Mariusz Kowalewski; Tomasz Jadczyk; Michał Laskiewicz; Marek Jędrzejek; et al. (PLoS ONE)
Background Interventional diagnostic and therapeutic procedures requiring intravascular iodinated contrast steadily increase patient exposure to the risks of contrast-induced acute kidney injury (CIAKI), which is associated with death, nonfatal cardiovascular events, and prolonged hospitalization. The aim of this study was to investigate the efficacy of pharmacological and non-pharmacological treatments for CIAKI prevention in patients undergoing cardiovascular invasive procedures with iodinated contrast. Methods and findings MEDLINE, Google Scholar, EMBASE and Cochrane databases as well as abstracts and presentations from major cardiovascular and nephrology meetings were searched, up to 22 April 2016. Eligible studies were randomized trials comparing strategies to prevent CIAKI (alone or in combination) when added to saline versus each other, saline, placebo, or no treatment in patients undergoing cardiovascular invasive procedures with administration of iodinated contrast. Two reviewers independently extracted trial-level data including number of patients, duration of follow-up, and outcomes. Eighteen strategies aimed at CIAKI prevention were identified. The primary outcome was the occurrence of CIAKI. Secondary outcomes were mortality, myocardial infarction, dialysis and heart failure. The data were pooled using network meta-analysis. Treatment estimates were calculated as odds ratios (ORs) with 95% credible intervals (CrI). 147 RCTs involving 33,463 patients were eligible. Saline plus N-acetylcysteine (OR 0.72, 95%CrI 0.57-0.88), ascorbic acid (0.59, 0.34-0.95), sodium bicarbonate plus N-acetylcysteine (0.59, 0.36-0.89), probucol (0.42, 0.15-0.91), methylxanthines (0.39, 0.20-0.66), statin (0.36, 0.21-0.59), device-guided matched hydration (0.35, 0.12-0.79), prostaglandins (0.26, 0.08-0.62) and trimetazidine (0.26, 0.09-0.59) were associated with lower odds of CIAKI compared to saline. Methylxanthines (0.12, 0.01-0.94) or left ventricular end-diastolic pressure-guided hydration (0.09, 0.01-0.59) were associated with lower mortality compared to saline. Conclusions Currently recommended treatment with saline as the only measure to prevent CIAKI during cardiovascular procedures may not represent the optimal strategy. Vasodilators, when added to saline, may significantly reduce the odds of CIAKI following cardiovascular procedures.